Simulating resource allocation for protecting public events - Wong, See Lai (2015)
With the rise in global terrorism, the need to ensure the safety of the public is greater than ever. Public events are very susceptible to terrorist attacks, although there are security resources that protect these event, there is the problem of allocating the resources effectively and efficiently. Many resource allocation algorithms has been proposed to resolve the problem. The objective of this project is to design and create a simulation model integrated with Geographic Information System (GIS) to simulate how systems behave in real-life using resource allocation algorithms and then use the data collected to evaluate the performance of these algorithms. For this project we designed the simulation model based on the article Game-theoretic Resource Allocation for Protecting Large Public Events" and test the model using the SCOUT-A algorithm proposed in the article. Repast Simphony is used to implement the simulation model and the model created is succesfully integrated with GIS, it is able to generate a 3D visualisation of geographic features based on real-world objects. Using Boston Marathon as an example to carried out simulations using SCOUT-A algorithm to allocated security resources, it is shown that SCOUT-A algorithm is more effective than general defense strategies.